Human Rights Perspectives on Resolving Medical Malpractice Cases through Penal Mediation in Indonesia - Suwito, Suwito; Sari, Liani; NGA, Pham Thanh; Towadi, Mellisa; Manullang, Sardjana Orba (Universitas Negeri Gorontalo, 2023)
This study aims to analyze human rights perspectives in resolving medical malpractice cases through penal mediation in Indonesia and the United States and find solutions to improve human rights protection in resolving such issues in Indonesia. The research was conducted by juridical normative research methods with a comparative approach, and the analysis was carried out by legal hermeneutics. The results showed that penal mediation in resolving medical malpractice cases needs to be improved in Indonesia to pay more attention to the human rights of victims and perpetrators, especially regarding equality and recognition of victims. In the United States, it is necessary to create consistent and detailed federal laws regarding penal mediation to resolve medical malpractice cases. The legal concept/regulation of human rights protection in resolving medical malpractice cases through penal mediation in Indonesia must ensure that the human rights of victims and perpetrators are protected and that the solutions found meet the needs of both parties fairly and humanely.